Manajemen Strategi Brand Equity Berbasis Pelanggan di Lingkungan Pondok Pesantren Bina Aksara Mulya DIY - Jamaludin, Muhamad; Rahmadi Bagus Wijaya; Firdaus (Education Reserach Center, 2025)
Customer-based brand equity strategy is one of the important approaches in improving the competitiveness of educational institutions, including Bina Aksara Mulya Islamic Boarding School, DIY. This research aims to analyze the customer-based brand equity strategy at Bina Aksara Mulya Islamic Boarding School, DIY. The main focus of the research is to identify factors that influence brand awareness, positive associations with the quality of education and religious traditions, and loyalty of students and alumni to the pesantren. The method used is qualitative research with a case study approach, involving observation, in-depth interviews, and document analysis. The results showed that: (1) increased awareness of the pesantren brand occurs through quality education programs, social activities that involve the community, and effective utilization of online media; (2) there are strong positive associations related to the quality of education, strong religious traditions, and an environment that supports the learning process. (3) The loyalty of santri and alumni is reflected in their contributions through donations, social assistance, and involvement in various pesantren activities. This study also found that the relationship between these brand equity elements is very mutually supportive, creating a good reputation for pesantren in the eyes of the community. These findings make an important contribution to the understanding of brand management in faith-based educational institutions